Nano-oxide precipitation kinetics during the consolidation process of a ferritic oxide dispersion strengthened steel. (November 2020) - Spartacus, Gabriel; Malaplate, Joël; De Geuser, Frédéric; Sornin, Denis; Gangloff, Amélie; Guillou, Raphaëlle; Deschamps, Alexis
Abstract: Oxide Dispersion Strengthened (ODS) steels are candidates for nuclear applications. ODS are produced by mechanical alloying of Fe-14Cr, Y2 O3 and TiH2 powders and consolidation at 1100  °C, resulting in finely dispersed nano-oxides. Their precipitation kinetics has been quantitatively determined by in-situ Small Angle X-ray Scattering during continuous heating up to 1100  °C. Clusters, found in the as-milled state start growing at 450  °C until 1100  °C, while almost no coarsening was recorded during subsequent isothermal annealing. The nano-oxides resulting from these in-situ experiments were found to be representative of those in materials processed by hot isostatic pressing and hot extrusion. Graphical abstract: Image, graphical abstract